Al-Ãwamil al-Lughawiyah wa Ghair al-Lughawiyah li ShuÃºbat QiraÃ¡h al-Nushush al-Ãrabiyyah (Bahts Maidany fi al-Shaf al-Tsamin bi Maâ€™had Mathlaâ€™ al-Anwar Pontianak - Sahrani, Sahrani; Yoviyani, Salis Hilda (Institut Agama Islam Negeri Curup, 2022)
The aims of this study were: 1) To determine the linguistic factor which is the biggest cause of difficulty in reading Arabic texts in class VIII students of Mathlaâ€™u al-AnwÃ¢r Pontianak in the academic year 2020/2021; 2) Knowing non-linguistic factors is the biggest cause of difficulty in reading Arabic texts by grade VIII students of Mathlaâ€™u al-AnwÃ¢r Pontianak for the 2020/2021 academic year. This study uses a quantitative approach using descriptive methods and the type of field research. The data collection instruments used oral and written tests, questionnaires and documentation. The data analysis technique that we used is quantitative data analysis with average analysis and factor analysis with confirmatory factor analysis techniques. The results of this study are: 1) The linguistic factor which is the biggest cause of difficulty in reading Arabic texts in Class VIII students of Mathlaâ€™u al-AnwÃ¢r Pontianak Academic Year 2020/2021 is a grammar factor with an average score of 42.35. 2) The non-linguistic factors that became the biggest cause of difficulty in reading Arabic texts in class VIII students of Mathlaâ€™u al-AnwÃ¢r Pontianak for the 2020/2021 academic year were student factors with an eigenvalue of 10.641 and a variance of 53.2%.Â